Creatinine and myoglobin are poor predictors of anaerobic threshold in colorectal cancer and health. Issue 2 (30th April 2015) - Nyasavajjala, Sitaramachandra M.; Phillips, Beth E.; Lund, Jon N.; Williams, John P.
Abstract: Aims: Myoglobin is a haem protein produced in skeletal muscles. Serum concentrations of myoglobin have been proposed as a surrogate marker of muscle mass and function in both cachectic cancer patients and healthy non‐cancer individuals. Creatinine, a metabolite of creatine phosphate, an energy store found in skeletal muscle, is produced at a constant rate from skeletal muscle. Urinary and plasma creatinine have been used in clinical practice as indicators of skeletal muscle mass in health and disease. Our study aimed to test the hypothesis that plasma myoglobin and creatinine concentration could accurately predict skeletal muscle mass and aerobic capacity in colorectal cancer (CRC) patients and matched healthy controls and thereby an indicative of aerobic performance. Methods: We recruited 47 patients with CRC and matching number of healthy volunteers for this study. All participants had their body composition measured by dual‐energy X‐ray absorptiometry scan, aerobic capacity measured to anaerobic threshold (AT) by cardiopulmonary exercise testing and filled in objective questionnaires to assess the qualitative functions. This study was carried out in accordance with the Declaration of Helsinki, after approval by the local National Health Service (NHS) Research Ethics Committee. Results: Age‐matched groups had similar serum myoglobin and creatinine concentrations in spite of differences in their aerobic capacity. AT was significantly lower in the CRC group compared with matched controls (1.18 ± 0.44 vs. 1.41 ± 0.71 L/min; P < 0.01). AT had significant correlation with lean muscle mass (LMM) among these groups, but myoglobin and creatinine had poor correlation with LMM and AT. Conclusions: Serum myoglobin is a poor predictor of muscle mass, and serum myoglobin and creatinine concentrations do not predict aerobic performance in CRC patients or healthy matched controls.